RELEVANCE OF DEVELOPING STUDENTS' SELF-PREPARATION IN DIGITAL EDUCATION CONDITIONS - Muslimov Narzulla Alikhanovich; Umarova Zakhro Abdurakhim qizi (Bright Mind Publishing, 2025)
The transformation of higher education through digitalization has heightened the importance of students’ ability to engage in effective self-preparation. This article examines the pedagogical and didactic foundations necessary to foster self-directed learning in digital environments. It emphasizes the development of transversal competencies—such as critical thinking, collaboration, and communication—and transformative competencies, including adaptability, self-reflection, and lifelong learning orientation. These competencies are essential for training T-shaped professionals capable of navigating the demands of modern digital education. The article argues for the integration of intentional instructional strategies and support systems to help students develop autonomy, motivation, and strategic learning skills in independent study.